Reclaiming Control as a Semantic and Pragmatic Phenomenon. - Duffley, Patrick J. (Pragmatics & beyond., 2014)
This monograph is part of a growing research agenda in which semantics and pragmatics not only complement the grammar, but replace it. The analysis is based on the assumption that human language is not primarily about form, but about form-meaning pairings. This runs counter to the autonomous-syntax postulate underlying Landau (2013)'s Control in Generative Grammar that form must be hived off from meaning and studied separately. Duffley shows control to depend on meaning in combination with inferences based on the nature of the events expressed by the matrix and complement, the matrix subject,